Authentication for document management - Kot, Alex Chichung. (2008)
The advancement in digital technology and multimedia has made it easy to duplicate, manipulate and illegally distribute the multimedia content. In addition, it is easy to forge an image with the availability of the powerful image editing software and digital cameras. In this report, we present five data hiding techniques for binary images authentication and tampering localization. In addition, to accurately evaluate the amount of distortions caused by flipping pixels in binary images, we propose an objective distortion measure. Ensuring the authenticity and integrity facilitates the management of digital documents. The relationship of two typical type of data hiding methods, i.e., pixel pattern and key-weight methods are discussed. Finally, two steganalysis methods to detect data hiding on binary cartoon and text images are presented such that secret communication can be monitored.